Burnout and occupational stressors among non-medical occupational health staff. (20th December 2019) - Okuda, Yukako; Iwasaki, Shinichi; Deguchi, Yasuhiko; Nitta, Tomoko; Mitake, Tomoe; Sakaguchi, Aya; Niki, Akihiro; Inoue, Koki
Abstract: Background: The work required to assist individuals in improving their mental health is stressful and known to be associated with burnout. In Japanese companies, non-medical occupational health (OH) staff often take the role of maintaining and improving workers' mental health. However, few studies have examined burnout in this population. Aims: To assess the relationship between burnout and occupational stressors among non-medical OH staff. Methods: We conducted a cross-sectional study of OH staff who had participated in mental health seminars between 2016 and 2018. Occupational stressors were assessed using the Japanese version of the Job Content Questionnaire. Burnout was assessed using the Japanese version of the Maslach Burnout Inventory. Results: We administered the survey to 230 non-medical OH staff, of which 188 completed the questionnaire. According to a hierarchical multiple linear regression analysis, high job demands were associated with greater emotional exhaustion, depersonalization and personal accomplishment. Greater job control was associated only with higher personal accomplishment. Lower job support was associated with greater emotional exhaustion and depersonalization. Conclusions: The present study found relationships between occupational stressors and burnout dimensions among OH staff. To avoid burnout among non-medical OH staff, it is important to take measures against occupational stressors, especially job demands and low levels of job support.